"Proyecto de desarrollo turístico del Cantón Mocha para impulsar el turismo de aventura." - Armendáriz Armendáriz, María Dolores (2016)
This survey is focus on at Mocha Canton. Because, it is one of most the places with great tourist potential but, it has not been exploited is why we propose to solve this problem. That is the main reason of this study to solve this problem. According to the market division in this area, there are a lot of tourist activities to do, nowadays the tourist request is high and therefore increases the demands, the needs and desires of customers. To get the results several studies were developed, such as: Diagnosis of the present situation, for this reason it has been decided to develop a project that promotes adventure tourism as the Mocha Canton, natural and cultural attractions that have not been exploited properly, which is why we developed this extraordinary research innovation tourism options will be provided, which has an important tourist potential with many traditions, customs, culture and extraordinary history. The purpose of the development of this research, the idea is that with the help of this development project adventure tourism boost, and so it possible to produce more tourism and economic movement in this canton, it needs to continue developing in terms of tourism.